Defect modified zinc oxide with augmenting sonodynamic reactive oxygen species generation. (August 2020) - Liu, Yang; Wang, Ying; Zhen, Wenyao; Wang, Yinghui; Zhang, Songtao; Zhao, Ying; Song, Shuyan; Wu, Zhijian; Zhang, Hongjie
Abstract: Poor chemical stability, low tumor enrichment, and weak therapeutic effects of commonly used organic sonosensitizers significantly hinder further clinical applications of sonodynamic therapy (SDT). Encouraged by the principles of semiconductor catalysis and defect chemistry, we obtained a defect-rich gadolinium (Gd) doped zinc oxide (D-ZnOx :Gd) semiconductor sonosensitizer by defect engineering for efficient deep tumor sonodynamic eradication. The abundant oxygen defect can promote the separation of the electron (e − ) and hole (h + ) of D-ZnOx :Gd, which significantly enhances the sonodynamic effect. In addition, D-ZnOx :Gd is more easier to adsorb water and oxygen molecules due to its rich oxygen-deficient, greatly enhancing the capacities of ROS production. A significantly higher sonodynamic ROS generation abilities and anti-deep tumor efficiency against breast cancer are obtained in such defect-rich ZnO nanobullets. This work not only broadens the applications of ZnO semiconductor nanoagent in the field of nanomedicine, but also reveals the mechanism of how the oxygen deficiency enhanced the sonodynamic efficacy of zinc oxide, providing a new application of defect engineering in the field of cancer therapy. Graphical abstract: Image 1